Giant tunnel magnetoresistance induced by thermal bias - Manaparambil, Anand; Weymann, Ireneusz (Journal of magnetism and magnetic materials, 2023)
We analyze the spin-resolved transport and, in particular, the tunnel magnetoresistance of an asymmetric ferromagnetic tunnel junction with an embedded quantum dot or molecule subject to thermal and voltage bias in the nonlinear response regime. We demonstrate that such system exhibits a giant tunnel magnetoresistance effect that can be tuned by gate and bias voltages. Large values of magnetoresistance are associated with the interplay between the Kondo correlations and the ferromagnetic-contact-induced exchange field. In particular, we show that the nonequilibrium current in the parallel and antiparallel magnetic configuration of the system changes sign at different values of the voltage and thermal bias. This gives rise to giant values of magnetoresistance, the sign of which can be controlled by the applied sources. •Quantum dots or molecules asymmetrically coupled to ferromagnetic leads under thermal bias can show giant tunnel magnetoresistance (TMR).•The currents induced by the potential and temperature gradients cancel out at different points for different lead configurations resulting in the giant TMR.•The sign and magnitude of the giant TMR can be tuned by the applied potential and thermal biases.